Impact of climate smart agriculture on households’ resilience and vulnerability: an example from Central Rift Valley, Ethiopia - Ali, H.; Menza, M.; Hagos, Fitsum; Haileslassie, Amare (Wiley, 2023)
Climate change is causing serious challenges for smallholder farm households, especially in sub-Saharan Africa. The overarching objectives of this study are as follows: (i) to estimate household resilience and vulnerability indices, (ii) identify factors that explain these indices and (iii) to examine the impact of climate-smart agriculture (CSA) on households’ resilience and vulnerability, and (iv) to identify which CSA package performs better in enhancing resilience and reducing vulnerability. For this study, 278 farm households from 4 districts and 8 kebeles from the Central Rift Valley (CRV) of Ethiopia were randomly selected using a three-stage proportional to size sampling procedure. Cross-sectional data applying a structured and pretested survey questionnaire was collected for 2020/21 production season. Household resilience and vulnerability indices were estimated using resilience index and measurement analysis and indicators approaches, respectively. Multinomial endogenous switching regression was used to estimate the average treatment effects (ATEs) of the adoption of CSA practices on households’ resilience and vulnerability. The results show that livestock holding, land size, level of education, and state of food consumption are major explaining factors of resilience, whereas educational level of households, livestock holding, and access to credit are found to be major factors explaining vulnerability. The estimated ATEs indicate that households which adopted more diversified combinations of CSA packages were more resilient and less vulnerable than non-adopter households. The impacts of soil fertility management and conservation agriculture practices have better performance in improving resilience, whereas conservation agriculture and small-scale irrigation performed better in reducing the vulnerability of rural households in CRV. Boosting resilience and reducing vulnerability, hence, requires scaling up CSA among smallholder farmers by diversifying and raising farm households’ income, educational status, and livestock holding.